METHODOLOGY FOR DEVELOPING THE EDUCATIONAL ACTIVITIES OF FUTURE GEOGRAPHY TEACHERS IN A DIGITAL LEARNING ENVIRONMENT - Sukhrob Sharob ogli Khujakulov,Pirnazarova Shahlo Boynazar kizi ,Khamrayeva Dilfuza Alisher kizi (Ethiopian International Journal of Multidisciplinary Research, 2025)
This article analyzes methodological approaches to developing the skills of future geography teachers in designing educational and professional activities within a digital learning environment. Pedagogical design methods based on digital resources specific to geography, geoinformation technologies, and modern lesson design are presented. These approaches provide practical justification for developing digital competencies in future educators, designing innovative lessons, and applying interactive methods.